Dampak fluktuasi kurs transaksi atas indeks sektoral di Indonesia - Christdeo Deva Rompas; Christian Imanuel Octavianus Tuhatelu (Yayasan Widyantara Nawasena Raharja, 2023)
The tendency of the IDR exchange rate to strengthen against the USD until the end of April 2023 implies conditions for good economic growth in Indonesia. The purpose of this study is to determine the relationship between the exchange rate and sector indices in Indonesia with an observation period from 1 January 2023 to 30 April 2023. This study finds that COMPOSITE, IDXINDUST, IDXPROPERT, IDXFINANCE, and IDXTRANS had a significant non-unidirectional relationship with changes in exchange rates. Other findings also show that IDXINFRA and IDXHEALTH have a significant unidirectional relationship with changes in exchange rates. However, the findings also show that IDXBASIC, IDXCYCLIC, IDXENERGY, IDXNONCYC, and IDXTECHNO tend to be more stable with changes in exchange rates.